Breeding bananas and plantains: from intractability to feasibility - Vuylsteke, D.R. (International Society for Horticultural Science, 2000)
Banana has long been considered intractable to genetic improvement as only landraces are cultivated despite 75 years of breeding endeavors. However, recent advances in several breeding programs have demonstrated that development of improved germplasm through conventional cross-breeding may eventually result in man-bred cultivars for local consumption and commercial production. Seed set rates are workable in many Musa subgroups. Insight into combining abilities, heterotic groups, and the genetics of qualitative and quantitative traits has been gained and is being applied to make breeding more efficient. A wide array of breeding schemes is being explored, combining conventional and innovative approaches, and producing potential cultivars from primary tetraploids, secondary triploids and other populations. A number of improved genotypes are undergoing multilocational evaluation, from which knowledge on genotype-byenvironment interaction and stability of important traits is acquired. Though some important Musa subgroups (Cavendish, False Horn plantain) remain recalcitrant to conventional breeding, biotechnology holds promise for their improvement. The recent interest in banana breeding was mainly sparked by the black sigatoka epidemic, to which resistance is now readily available. Other major production constraints, particularly nematodes, fusarium and virus, are now receiving increased attention from breeders. Further progress in breeding may help to make banana a modern crop.